Designing a Distance Course for Developing the Art Teachers’ Media and Information Literacy - Havrilova, Liudmula; Beskorsa, Olena; Ishutina, Olena (Educological discourse, 2023)
Currently, media literacy is a necessary component of the general information culture of a person, which becomes absolutely crucial in the conditions of Russia’s military aggression and the harsh realities of the Ukrainian information space with numerous examples of spreading untrue, unverified, and “fake” information. In recent years, the concept of “media information literacy” (MIL) has become normalized in scientific circulation. It implies recognition of the leading role of information and media in everyday life, enables citizens to understand the functions of mass media and other information providers, critically evaluate their content and make informed decisions. In the documents of UNESCO and the European Commission, the concept of MIL is used as a universal term that denotes a set of knowledge, attitudes, abilities, and skills that allow access to information and knowledge, analyse, evaluate, use, create and disseminate them with maximum productivity in accordance with legislative and ethical standards and with respect for human rights. The article highlights the process of designing the distance course “Media Literacy in Art Classes” for teachers of general secondary education institutions that teach the courses of the art cycle, in particular, the integrated course “Art”. Scientific sources and legal documents were analysed to clarify the essence and modern interpretation of the concept of “media information literacy”; a number of mass open online courses on media literacy were considered; a survey of art teachers was conducted. According to the results of the survey, 6 topics, which were the most interesting to the respondents, were selected and the structure of the distance course, designed for 30 hours, 1 ECTS credit, was formed. The content of the course includes the study of the peculiarities of perception and critical evaluation of visual and audiovisual arts, as well as various aspects of the impact of media arts on the content of media messages. The course can be offered to teachers, especially teachers of primary school and courses in the educational field “Art”, as a certification programme in the system of advanced training.